2009
DOI: 10.1890/08-2025.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the carbon cycle in the Arctic to climate change

Abstract: Abstract. The recent warming in the Arctic is affecting a broad spectrum of physical, ecological, and human/cultural systems that may be irreversible on century time scales and have the potential to cause rapid changes in the earth system. The response of the carbon cycle of the Arctic to changes in climate is a major issue of global concern, yet there has not been a comprehensive review of the status of the contemporary carbon cycle of the Arctic and its response to climate change. This review is designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
810
8
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 904 publications
(844 citation statements)
references
References 252 publications
(305 reference statements)
22
810
8
4
Order By: Relevance
“…Some evidence showed that terrestrial ecosystems (e.g., tundra) might be a weak C sink rather than a C source under global climate warming [Shaver et al, 2000;Smith et al, 2004;Zimov et al, 2006b;Hollingsworth et al, 2008;McGuire et al, 2009;Zhuang et al, 2010;Elmendorf et al, 2012;Lu et al, 2012], but other evidence points in the opposite direction [Belshe et al, 2013;Natali et al, 2014]. Our short-term and 50 year long projection showed that annual warming and winter warming increase the C sink strength rather than decrease C. Our study support that the tundra ecosystem will remain as a weak C sink at least in the first half of this century.…”
Section: Resultsmentioning
confidence: 99%
“…Some evidence showed that terrestrial ecosystems (e.g., tundra) might be a weak C sink rather than a C source under global climate warming [Shaver et al, 2000;Smith et al, 2004;Zimov et al, 2006b;Hollingsworth et al, 2008;McGuire et al, 2009;Zhuang et al, 2010;Elmendorf et al, 2012;Lu et al, 2012], but other evidence points in the opposite direction [Belshe et al, 2013;Natali et al, 2014]. Our short-term and 50 year long projection showed that annual warming and winter warming increase the C sink strength rather than decrease C. Our study support that the tundra ecosystem will remain as a weak C sink at least in the first half of this century.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that Arctic streams export a greater proportion of primary productivity as compared to temperate and tropical watersheds (Peterson et al 1986;Harvey et al 1997;Waddington and Roulet 1997;McGuire et al 2009). As temperatures warm in the Arctic and soils thaw, the balance of C fixed by plants and released, either to the atmosphere as CO 2 or CH 4 or in streams as DOC or dissolved inorganic C, is expected to change (McGuire et al 2002(McGuire et al , 2009), but the magnitude and direction of this change is unknown.…”
Section: Changes In C and N Flux In The Kuparuk Rivermentioning
confidence: 99%
“…A significant proportion of primary production in Arctic ecosystems is exported as dissolved and particulate organic C in rivers (McGuire et al 2009), and mobilization of terrestrial nutrients during high-discharge events drives productivity in oligotrophic lakes and streams (Hobbie et al 1999;MacIntyre et al 2006). Constituent concentrations in Arctic streams vary with changing discharge due to snowmelt and/or rainfall as observed in many other places around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The typical cold conditions at high latitudes strongly constrain decomposition of organic material (McGuire et al 2009) and over time this has led to the build-up of organicmatter rich soils with relatively slow nutrient cycles in this region. As a consequence, northern high latitude soils store almost 30% of the global soil carbon (C) stocks (Scharlemann et al 2014), even if they only cover ca.…”
Section: Introductionmentioning
confidence: 99%